2020
DOI: 10.2105/ajph.2020.305619
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toll of Untreated Perinatal Mood and Anxiety Disorders Among 2017 Births in the United States

Abstract: Objectives. To estimate the economic burden of untreated perinatal mood and anxiety disorders (PMADs) among 2017 births in the United States. Methods. We developed a mathematical model based on a cost-of-illness approach to estimate the impacts of exposure to untreated PMADs on mothers and children. Our model estimated the costs incurred by mothers and their babies born in 2017, projected from conception through the first 5 years of the birth cohort’s lives. We determined model inputs from secondary data sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 59 publications
1
150
0
Order By: Relevance
“…Perinatal anxiety rates were approximately six times higher in this sample compared to pre-pandemic perinatal rates in Colorado. 29 Additionally, participants reported lower well-being 30 and lower levels of resilience compared to pre-pandemic scores. 26 The qualitative component of this study illustrated sources of stress that further explain these quantitative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal anxiety rates were approximately six times higher in this sample compared to pre-pandemic perinatal rates in Colorado. 29 Additionally, participants reported lower well-being 30 and lower levels of resilience compared to pre-pandemic scores. 26 The qualitative component of this study illustrated sources of stress that further explain these quantitative findings.…”
Section: Discussionmentioning
confidence: 99%
“…They found that it cost $32,000 for each mother‐child dyad that was affected but untreated. In 2017, this cost the United States an estimated $14.2 billion . Sixty percent of these costs were attributed to maternal outcomes and the remaining 40% to child outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings represent a unique contribution to the evidence base on the burden of PPD since healthcare costs attributed to PPD have not been previously studied in a comprehensive manner, especially those that might be attributed to the partner and other dependent children in the household. Recent literature has noted that the economic burden of perinatal mood and anxiety disorders in the US was high 25 , however like other studies 24 , was limited to only mother and child economic outcomes. Including household cost comparisons widens the perspective of the large economic PPD incurs and will help inform future cost estimates and analyses.…”
Section: Discussionmentioning
confidence: 91%
“…While the individual and familial psychosocial and developmental consequences of PPD are clear, there is currently limited information about the economic impact of PPD. A recent research based on a cost-of-illness model found that the economic burden of perinatal mood and anxiety disorders in the US was high, with untreated disorders costing about $14 billion for the 2017 birth cohort from conception to 5 years postpartum 25 . While this research combined published estimates of direct healthcare costs and indirect societal costs, it focused only on longer term economic burden of untreated perinatal mood and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%